2020
DOI: 10.17711/sm.0185-3325.2020.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hormonal and metabolic factors related to depression in reproductive age women

Abstract: Introduction. Major depressive disorder (MDD) is a prevalent disease affecting women more than men worldwide. Various factors are involved in the genesis of depression, including hormones such as testosterone and certain metabolic factors Objective. To evaluate hormone levels and metabolic variables in women with major depression and healthy controls. Method. A cross-sectional, comparative analytical study was conducted in 40 participants, 23 patients with an MDD diagnosis and 17 controls, all of women in repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Instead, targeting the estrobolome in the prevention and treatment of these specific disorders could be an effective interesting approach, as estrogen levels may be directly influenced by the gut microbiota and women may benefit from the actions of these bacteria. It is also of note that some studies have reported that lower levels of testosterone but not estrogen were associated with more severe depressive symptoms in a group of 23 women with MDD [194]. In this context, Markle et al [195] reported that gut microbiota transplantation from male to female mice led to an augmentation of testosterone levels and metabolomic changes in females and future studies may consider the benefits from using testosterone-producer microorganisms to raise testosterone levels.…”
Section: Estrobolomementioning
confidence: 98%
“…Instead, targeting the estrobolome in the prevention and treatment of these specific disorders could be an effective interesting approach, as estrogen levels may be directly influenced by the gut microbiota and women may benefit from the actions of these bacteria. It is also of note that some studies have reported that lower levels of testosterone but not estrogen were associated with more severe depressive symptoms in a group of 23 women with MDD [194]. In this context, Markle et al [195] reported that gut microbiota transplantation from male to female mice led to an augmentation of testosterone levels and metabolomic changes in females and future studies may consider the benefits from using testosterone-producer microorganisms to raise testosterone levels.…”
Section: Estrobolomementioning
confidence: 98%
“…In addition, phthalates can also promote a Th2 differentiation, the above has been reported in vivo, in vitro, and epidemiological studies in asthma [38,39]. Some research groups have examined the serum levels of E2 in patients with MDD, which are around 85-127 pg/ml and 55 pg/ml in the female and male population, respectively [40,41]. To date there are many studies about the quantification of phthalates and bisphenols in different biological fluids [42][43][44][45].…”
Section: Introductionmentioning
confidence: 98%
“…Some research groups have examined the serum levels of E2 in patients with MDD, which are around 85-127 pg/mL and 55 pg/mL in the female and male population, respectively [38,39]. To date, there are many studies about the quantification of phthalates and bisphenols in different biological fluids [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%